Treatment of luminal HER2-negative breast cancer: opinion of experts - E. V. Artemeva; M. L. Makarkina (Лечащий Врач)
The discussion, dedicated to the treatment of luminal HER2-negative breast cancer stages II and III, was attended by doctors from St. Petersburg – Maria Leonidovna Makarkina, M.D., oncologist of the outpatient department of the N. P. Napalkov Cancer Center, and Elizaveta Vladimirovna Artemyeva, oncologist of the inpatient department of antitumor drug therapy No. 1 of the N. P. Napalkov Cancer Center.